STRUCTURAL OPTIMIZATION AND FATIGUE LIFE STUDY OF AIR HAMMER BIT - FENG ChunYu; YANG ShuangQing; FAN LiMing; LIU HanGuang; LAI ShuBin; LIU YuanRi (Jixie qiangdu)
Due to the low fatigue life of the air hammer bit in the drilling process, the drilling efficieney is greatly reduced and the drilling cost is increased. Therefore, the fatigue life of the air hammer bit is studied and its structure is optimized to improve the service life of the air hammer bit. On the basis of the 12.25 in (1 in = 2.54 cm) air hammer bit. the overall structure of the air hammer bit was designed considering the anti-drop structure. The concept of micro bit was proposed and the fatigue life experiment of miero bit samples was completed, using Ansys/Ls-Dyna and nCode DesignLife software, the dynamics and fatigue life of the micro drill bit are analyzed and verified with the experimental results, and the basie structure and material of the drill bit are determined. The simulation process is applied to the drill bit body, considering the size of the drill bit body and the impact velocity of the piston, etc. The influence of the problem on the fatigue life of the drill bit, the structure of the drill bit is optimized. The research shows that the drill bit with 40CrMnSiMoV has the best fatigue life. Among the basic dimensions of the drill bit body, the diameter has the greatest impact on the fatigue life of the drill bit. When the impact energy changes, the fatigue life of the drill bit decreases with the increase of the end speed. When the impact energy is constant, when the square of the end speed of the drill bit is close to the quality of the drill bit, the fatigue life of the drill bit is the best.